Research at an undergraduate level - An insight into its importance - Ram, Pradhum; Sethi, Akshay; Madadin, Mohammed; Menezes, Ritesh G (Nepal Journal of Epidemiology, 2016)
In the world of evidence-based medicine, the need for research cannot be overstated. While the helm of such research if being conducted by trained scientists in secluded labs, one often forgets that these scientists were students too at one point in time. If their interest was not honed then, we might still be fighting polio today. Thus with this editorial we hope to usher more students into research at the undergraduate level.